Serogrouping of beta-hemolytic streptococci from throat swabs with nitrous acid extraction and the Phadebact streptococcus test. - Slifkin, M (1982)
A direct extraction of the antigen of group A beta-hemolytic streptococci from 373 throat swabs was done with a microtechnique of the nitrous acid extraction-Phadebact coagglutination method. The technique yielded a 96% agreement with the results obtained by a standard throat culture method in which the Phadebact grouping procedure with overnight broth supernatants was employed.